Proyecto de factibilidad para la creación de una panadería en la parroquia Zumba del cantón Chinchipe, provincia de Zamora Chinchipe - Abarca Villacis, Maricela Patricia (2023)
The research work aims to determine the feasibility for the creation of a bakery in the Zumba parish, based on market, technical, administrative, legal, and economic-financial studies. This work focused on a quantitative-qualitative investigation and is descriptive in nature. Techniques such as observation, interviews, and surveys were used. The total population of the Zumba parish for the year 2022 is 8,116 inhabitants, comprising 2,135 families. There are 4 bakeries to assess the supply. The products that will be offered to families will be 6 varieties of bread, including sweet bread, salt bread, corn bread, Swiss bread, pizza bread, and onion and cheese bread, which were the most demanded. Upon analyzing the results, the effective demand for bread units is 4,584.883, the supply of units is 2,694,500.00, and the unsatisfied demand is 2,160.383. The used capacity will be 756,000 units. The economic-financial study indicates that $24,179.71 is required. $17,507.73 will be generated in the first year, and financial indicators show that the NPV exceeds the initial investment, with a profit of $32,684.99. The IRR will be 63.15%, and the RBC will be $0.21 cents. The time it will take to recover the investment will be 1 year, 4 months, and 2 days. The sensitivity analysis is 0.94 with an increase in costs of 8.13%, and the sensitivity analysis is 0.96 with a decrease in revenue of 6.56%. In other words, this project is not sensitive if there is an increase in costs or a decrease in revenue. It is concluded that, according to the aforementioned indicators, the establishment of this company is feasible.